The Role of Marital Satisfaction of Mothers on Anxiety Disorders and Mental Representation of Their Children: A Mix Method Study - Sepideh Ramzi; Zeynab Bahrami; Hadi Bahrami Ehsan; Atena Heydari (International Journal of Psychosocial Rehabilitation, 2020)
The present study was conducted to a) investigate the association between marital satisfaction of mothers and anxiety disorders in their children, b) compare anxiety disorders of children in three groups of divorced, distressed, and healthy families, and c) compare mental representation of children about the concept of the self, their parents, the quality of relationship between their parents and the world, and finally the main theme of their conflicts and anxieties in these three family groups. The research samples included 135 daughters (6-12 years old) and 125 mothers (mean age = 38 years) who were in three groups of divorced, distressed, and healthy families. The quantitative and qualitative methods were to analyze the research data. The results showed that there was a negative and significant relationship between marital satisfaction of mothers and children‘s anxiety disorders. The ANOVA results also showed that there were statistically significant differences in the levels of general anxiety and panic disorder in three groups, which were higher in children belonging to divorced and distress families rather than healthy ones. The results of content analysis of children‘s story based on Children Apperception Test (CAT) showed that children from divorced and distressed families mostly represented the concept of self, parents, the quality of their parent’s relationship, and the world in negative, threatening, and unsecured patterns. These children reflected more conflicts and anxiety with the nature of their parent’s relationship in their stories.